(untitled) (Journal of Global Accounting, 2023)
This study examined the effect of green accounting cost on return on equity, shareholders’ fund, earnings per share, profit after tax, and net profit margin of selected oil and gas companies. The study covered a time frame of thirteen (13) years that is, from 2020 to 2022 based on available data from the annual reports of the concerned companies. The study employed an ex-post facto research design with the aid of the Panel Ordinary Least Square (POLS) and Granger Causality techniques to analyse the data. The result of Granger Causality test revealed that green accounting cost has no significant effect on return on equity, shareholders’ fund, earnings per share, and net profit margin of oil and gas companies. In view of the findings, management of oil and gas companies in Nigeria should develop a well-articulated environmental costing system in order to guarantee a conflict free corporate atmosphere for improved return on equity.